ATTITUDE OF UNDERGRADUATE MEDICAL STUDENTS TO PATIENT SAFETY (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2018)
Background: To assess undergraduate medical students’ attitudes to the patient safety issue and their interest in patient safety education. Method: The cross-sectional survey of 519 undergraduate students was conducted at the Faculty of Medicine, Universitas Yarsi, in September 2017. A structured and anonymous self-administered questionnaire was handed to medical students, including preclinical and clinical undergraduate students. Results: Overall, 308(59%) students agreed that medical errors were inevitable, but 391(75%) students thought competent physicians do not make errors. More than half of the students said medical errors should be reported even if there is no harm to the patient (59% and 73% respectively). Less than half (29%) students believe reporting systems do little to reduce future errors. Almost all of the students (94%) thought work harder and more careful is an effective strategy after an error occurs. Over 80% of students thought physicians routinely share information about medical errors. The majority agreed that patient safety should be part of medical curriculum and physician should spend their time to improve patient care (66% and 86% respectively). Most students (94%) would like to receive teaching on patient safety further. Conclusion: This study revealed that undergraduate students had a positive attitude to patient safety and teaching of 'patient safety' needs to be promoted in the medical curriculum. Keywords: patient safety, medical error, curriculum, medical students